FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN BEI SEKTOR MAKANAN - Jasmadeti Jasmadeti; Wulan Wahyuni (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the factors that influence the capital structure of the Indonesian Stock Exchange in the food sector. The data source used in this research is secondary data. Data is sourced from audited annual reports obtained from the IDX official website, namely www.idx.co.id. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange, with research samples in the Food sector in the 2013-2017 period. The samples were determined using purposive sampling method. The method of analysis used in this research is multiple regression with the SPSS version 21 program and hypothesis testing is done using multiple linear regression method. The results of this study indicate that Profitability has no effect on capital structure with a significance value of 0.132. Asset Structure has no effect on capital structure with a value of 0.506. Meanwhile, Liquidity has an effect on capital structure with a significance value of 0.000. As well as Profitability, Liquidity, and Structure Asset simultaneously affect capital structure.